Beyond 'cure' and 'treatment success': quality of life of patients with multidrug-resistant tuberculosis - Laxmeshwar, C; Stewart, A G; Dalal, A; Kumar, A M V; Kalaiselvi, S; Das, M; Gawde, N; Thi, S S; Isaakidis, P (The international journal of tuberculosis and lung disease, 2019)
Two drug-resistant tuberculosis (DR-TB) sites (MSF Clinic, Jupiter Hospital) in Mumbai, India. To assess health-related quality of life (HRQoL) and associated factors among DR-TB patients and explore their perspectives about HRQoL. We used a mixed-methods design: a quantitative cross-sectional questionnaire (the World Health Organization's Quality of Life Brief Questionnaire [WHOQoL-BREF]); and qualitative in-depth interviews for purposively selected patients. Assessments were conducted between April and November 2016. Ninety-five patients completed WHOQoL-BREF; 12 were interviewed. The psychological and physical health domains were the most affected (mean scores 56.2 ± standard deviation [SD] 18.3, and 56.5 ± SD 15.1, respectively; maximum 100). The social relations and environmental domains mean scores were respectively 68.6 (SD ±21.1) and 60.3 (SD ±15.9). Loss of jobs due to TB adversely affected the social relations and environmental domains. Qualitative analysis showed that support was the most important theme affecting quality of life. Other themes were physical factors (e.g., treatment adverse events), psychological factors (e.g., depression), social functioning (e.g., fear of stigmatisation) and environmental factors (e.g., health systems). HRQoL was lower among study participants, but not as low as previously reported among TB patients. Support was the main factor that positively affected HRQoL, although both disease and treatment were physically and socially challenging.